Улучшение параметров качества тестирования радиотракта на абонентском участке - Кадацкая, О. И.; Сабурова, С. А. (ХНУРЭ, 2011)
In this work technique for productivity analysis of distributed systems with service oriented architecture (SOA) is presented. The technique is based on a hierarchical model using timed coloured Petri nets mathematical tool. In contrast to existing approaches it allows to study performance of SOA systems on the basis of different developers' solutions paying a great attention to characteristics of telecommunication infrastructure which is used for information exchange and transmission.
Keywords: проблема интеграции приложений; Service-Oriented Architecture